Bioindication of heavy metals in aquatic environment using photosynthetic pigments in cyanobacteria - Nurul Aisyah, Wan Jusoh; Chai, Mee Kin; Wong, Ling Shing; Ong, Ghim Hock; Wan, Betty Voon Niu (Elsevier, 2020)
Freshwater resources is seriously threatened by heavy metals pollution. Thus developing an effective screening method for the presence of heavy metals is required. In this paper, the potential of using cyanobacteria for heavy metals detection in water bodies is determined. The cyanobacteria Anabaena cylindrica had been cultured, immobilized, and exposed to Cu, Pb, and Cd with the concentrations of 0.01 – 10.00 mg/L. The responses of the cells to the heavy metals were measured for 60 min. The effect of the cell culture age and cell density were determined as well. The cells with 7 days of culture age, and the amount of cell with density of OD= 0.5 A (measured at 700 nm wavelength) were found to produce highest photosynthetic fluorescence for the detection for heavy metals. The cells were capable to provide detectable fluorescence emission within 10 min of exposure. Thus the cyanobacteria was identified as a good candidate to serve as bioindicator for the heavy metals in water.